Bioactivity and composition of lipophilic metabolites extracted from Antarctic macroalgae - Berneira, Lucas M. (2021)
Macroalgae comprise a vast group of aquatic organisms known for their richness in phytochemicals. In this sense, the lipophilic profile of five Antarctic seaweed species was characterized by chromatographic and spectroscopic analysis and their antioxidant and antimicrobial potential was evaluated. Results showed there were 31 lipophilic substances, mainly fatty acids (48.73 +/- 0.77 to 331.91 +/- 10.79 mg.Kg(-1)), sterols (14.74 +/- 0.74 to 321.25 +/- 30.13 mg.Kg(-1)), and alcohols (13.07 +/- 0.04 to 91.87 +/- 30.07 mg.Kg(-1)). Moreover, Desmarestia confervoides had strong antioxidant activity, inhibiting 86.03 +/- 1.47% of the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical at 1 mg.mL(-1). Antimicrobial evaluation showed that extracts from Ulva intestinalis, Curdiea racovitzae, and Adenocystis utricularis inhibited the growth of Escherichia coli (ATCC 25922), Staphylococcus aureus (ATCC 25923), and Salmonella typhimurium (ATCC 14028) from concentrations of 1.5 to 6 mg.mL(-1). Therefore, the evaluated brown, red, and green macroalgae contained several phytochemicals with promising biological activities that could be applied in the pharmaceutical, biotechnological, and food industries.